2018
DOI: 10.1177/0003702818803943
|View full text |Cite
|
Sign up to set email alerts
|

Improved Analysis of Manganese in Steel Samples Using Collinear Long–Short Double Pulse Laser-Induced Breakdown Spectroscopy (LIBS)

Abstract: A long-short double pulse laser-induced breakdown spectroscopy (long-short DP-LIBS) method was employed to improve the analytical performance of LIBS for the measurement of manganese in steel samples. The long pulse with a duration of 60 μs was generated using a neodymium-doped yttrium aluminum garnet (Nd:YAG) laser which was operated at free-running (FR) mode. To investigate the detection ability without sample preparation, the steel washers were tested using single-pulse LIBS (SP-LIBS) and long-short DP-LIBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 48 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…The results showed that the R 2 of calibration curve was improved from 0.810 to 0.988 using long-short DP-LIBS compared to SP-LIBS. In addition, the RSD was reduced from 29.3% (SP-LIBS) to 10.5% (long-short DP-LIBS) [52].…”
Section: Double Pulse Methodsmentioning
confidence: 93%
“…The results showed that the R 2 of calibration curve was improved from 0.810 to 0.988 using long-short DP-LIBS compared to SP-LIBS. In addition, the RSD was reduced from 29.3% (SP-LIBS) to 10.5% (long-short DP-LIBS) [52].…”
Section: Double Pulse Methodsmentioning
confidence: 93%
“…Thus FR laser pulse has lower energy density which is not enough to produce an observable plasma emission. [25][26][27] A short pulse laser with wavelength of 1 064 nm, pulse width of 5-8 ns, pulse energy of 24.5 mJ and frequency of 10 Hz is generated by the Laser (LOTIS TII, LS-2134U). The reflected short pulse laser beam combined with the long pulse laser beam by polarization prism to realize the collinear long-short DP-LIBS.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 lists the elemental compositions of standard steel sample and the iron content was obtained by subtracting the other major elements. 27) The sample were heated to the specified temperature in the muffle furnace, and the muffle furnace was operated at the atmosphere environment. The sample temperature varied as 20°C, 300°C, 500°C and 700°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long and short double-pulse LIBS method was proposed by our group and it has been named as LS-DP-LIBS [28,29]. In previous studies [30,31], LS-DP-LIBS has been compared with SP-LIBS based on the measurement results in an air atmosphere. Those studies have demonstrated that the plasma is enhanced and stabilized by LS-DP-LIBS.…”
Section: Introductionmentioning
confidence: 99%